Screening of tropical medicinal plants for sporicidal activity - Lau, Kah Yan; Rukayadi, Yaya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Bacterial spores have special significance in foods because they are much more resistant to physical and chemical antimicrobial treatment. Nowadays, there is interest in using natural products such as plant extract for food preservation. In this study, 26 of tropical medicinal plants and spices were screened for their sporicidal activity against the spores of Bacillus cereus. The spores of B. cereus was harvested after incubation at 30°C for 1 week and treated with various plant extracts using the method of Standard Operating Procedure for the AOAC (Association of Official Analytical Chemists) Sporicidal Activity. Glutaraldehyde was used as a positive control. Among them, Indonesian bay leaf (Eugenia polyantha Wight) inactivated more than 3 log of spores/ml of B. cereus (99.99%) at the concentration of 1% and completely killed B. cereus spores at concentration of 2.5%. These results suggest that Indonesian bay leaf extract has strong sporicidal activity against spores of B. cereus.